The Glow of Unwork? Issues of Portrayal in Arts-Related Research (LEARNing Landscapes, 2016)
In this paper we argue that arts-related research provides greater or diverse opportunities to represent and portray data di erently and suggest that these ways are underutilized. For example, for many researchers legitimacy comes through the use of participants’ voices in the form of quotations. However, we argue that this stance towards plausibility and legitimacy is problematic and needs to be reconsidered in terms of understanding di erences in types of portrayal, recognizing how researchers position themselves in relation to portrayal, and understanding decision-making in relation to portrayal.
Keywords: portrayal; legitimacy; ats-related research; decision making; positioning